Challenges of Migrating Legacies Web to Mobile: A Systematic Literature Review - Cajas, Viviana Elizabeth (2020)
The multi-device era comes thanks to mobile computing which gives remote access to resources from anywhere changing the people’s life and opening new business opportunities. However, the legacy systems do not render the content properly in mobile devices because they were thought to be only compliant with Web browsers. Economic availability is often the reason why these have not been modernized. This work proposes a systematic literature review about the approaches used for the portabilization or modernization of web 1.0 business applications to mobile devices in the period 2006-2017, from SCOPUS, IEEE, and ACM. The search obtained 824 articles, where 37 were selected based on the inclusion criteria. The research questions were: PI1. What have been the contribution to the portability of business applications to mobile devices? PI2. What methods have been used? PI3. What is the nature of the contribution found? PI4. What are the objectives that are pursued in the research work?. The conclusions were obtained through the classification of selected papers with respect to focus, scope, type of research and type of contribution to give an answer to research questions. Then, the state of the art determines the main approaches such as model-driven development, content reorganization, augmentation, and specific migrations. However, certain research gaps were detected and detailed which represent exploration opportunities.